2016
DOI: 10.4174/astr.2016.90.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic para-aortic lymph node dissection for patients with primary colorectal cancer and clinically suspected para-aortic lymph nodes

Abstract: PurposeTreatment of patients with para-aortic lymph node metastasis from colorectal cancer is controversial. The goal of this study was to investigate the technical feasibility of laparoscopic intrarenal para-aortic lymph node dissection in patients with colorectal cancer and clinically suspected para-aortic lymph node dissection.MethodsThe inclusion criteria for the laparoscopic approach were patients with infrarenal para-aortic lymph node metastasis from colorectal cancer. Patients who had any other distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 19 publications
3
72
0
Order By: Relevance
“…Nevertheless, despite recent advances in diagnostic imaging, it remains difficult to diagnose PALN metastases before surgery. It has been reported that approximately 60% of patients with a preoperative diagnosis of PALN metastasis who underwent para‐aortic lymphadenectomy were not diagnosed with pathological PALN metastasis . Primary resection is obviously the best primary treatment for patients without PALN metastasis, and given the present study’s favorable outcomes, it is reasonable to consider primary resection and laparoscopic para‐aortic lymphadenectomy for suspected isolated PALN metastasis from CRC.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, despite recent advances in diagnostic imaging, it remains difficult to diagnose PALN metastases before surgery. It has been reported that approximately 60% of patients with a preoperative diagnosis of PALN metastasis who underwent para‐aortic lymphadenectomy were not diagnosed with pathological PALN metastasis . Primary resection is obviously the best primary treatment for patients without PALN metastasis, and given the present study’s favorable outcomes, it is reasonable to consider primary resection and laparoscopic para‐aortic lymphadenectomy for suspected isolated PALN metastasis from CRC.…”
Section: Discussionmentioning
confidence: 80%
“…For patients with primary CRC and clinically suspected PALN metastasis who undergo para-aortic lymphadenectomy, open approaches are generally selected, and there have been very few reports about the use of laparoscopic approaches (4,5,9,10). The complication rates for open approaches remain high (range, 25%-50%) (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate is > 95% in rectal cancer patients without LN metastasis, but decreases to 50~ 70% in patients with LN metastasis [ 3 ]. Additionally, the LN stage of rectal cancer is one of the most important determining factors for adjuvant chemotherapy and extended LN dissection [ 21 , 22 ]. The procedure of choice for rectal cancer patients with a clinical stage of N0 or N1 is total mesorectal excision, which is surgical excision of the mesorectal fat, including all LNs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, postoperative morbidity occurred in 31.0% of patients, which was comparable with that of other studies (7.8-38.9%). [10][11][12][13][14] The main morbidity was surgical site infection, and the rate of Clavien and Dindo classification grade Ⅲ or above was only 10.3%, with no perioperative death. These results suggest that the incidence of postoperative morbidities associated with PALN dissection is within acceptable limits.…”
Section: Discussionmentioning
confidence: 99%